Mengatasi Tantangan Pembelajaran Online bagi Anak Tunagrahita Selama Pandemi: Peran Orang Tua dan Strategi Efektif - Astri Lestari; Dwi Ayu Nurani; Khodijah Khodijah; Sahlana Izyan Zaina; Salman Zakariya Dahlan; Siti Hamidah (Simpati, 2024)
This study examines the strategies and implications of online learning for children with intellectual disabilities during the COVID-19 pandemic. Children with special needs, including those with intellectual disabilities, require education tailored to their unique needs. This research uses a literature review method, prioritizing research articles published in the last 5 years to gather relevant data on distance learning and effective strategies for children with intellectual disabilities. The COVID-19 pandemic has forced a shift from face-to-face to online learning, posing significant challenges for children with intellectual disabilities who have difficulty with logical thinking and require direct interaction to understand material. Online learning offers advantages such as time flexibility and the use of technology, but also has drawbacks such as a lack of direct interaction, resulting in a limited understanding of the material. Parents play a crucial role in supporting children during online learning, but they face challenges such as limited knowledge and motivation from the child. This study found that parents often struggle to explain material to their children and maintain their learning motivation. To overcome these obstacles, recommended strategies include the use of simple language, repetitive explanations, and real-life examples. Online learning also brings children and parents closer, allowing parents to better understand their child's nature and create a closer relationship. In conclusion, support from family and teachers is essential to enhancing the effectiveness of online learning for children with intellectual disabilities, and adapting appropriate strategies can help overcome various challenges encountered during the online learning process during the pandemic.